EMISSIONS FROM BIOMASS OPEN BURNING ON THE PEAT SOIL IN INDONESIA: INTEGRATING MODIS IMAGERY AND GIS DATA - Ayu Utami; Chih-Hua Chang (Jurnal Ilmiah Lingkungan Kebumian, 2015)
Biomass open burning emissions release large amounts of pollutant, which has significantly contributed to the atmospheric pollution. This phenomenon also generates many pollutants as major influence on climate change. Southeast Asia currently has vast areas committed to agriculture, which are a major contributor of biomass open burning emissions. Satellite imagery and remote sensing are used in this study to calculate the burned area and emissions in the spatial context of Southeast Asia. The aim of this research is to obtain the importance of peat soil burning in Indonesia affected the amount of biomass open burning emissions in Southeast Asia. The burning of peat soil in Indonesia also emits large of emissions, thereforethiscasehastakenasaspecifictopicinthis research. MODIS burned area and land cover data products were used to detect the burned areas and estimate the emission factor in Southeast Asia related to emissions calculation. Asaresultofthisresearch,on 2001-2007, on May to October, Indonesia contributes a significant amount; approximately80%ofthetotalburnedin Southeast Asia wasoccurredinIndonesia. Data and results from this research can be applied for regulatory consideration to countries that participate in the Southeast Asia governing body.